Selective Release of Recombinant Periplasmic Protein From E. coli Using Continuous Pulsed Electric Field Treatment - Schottroff, Felix; Kastenhofer, Jens; Spadiut, Oliver; Jaeger, Henry; Wurm, David J. (Frontiers in Bioengineering and Biotechnology, 2021)
To date, high pressure homogenization is the standard method for cell disintegration prior to extraction of cytosolic and periplasmic protein from E. coli. Its main drawback, however, is low selectivity and a resulting high load of host cell contaminants. Pulsed electric field (PEF) treatment may be used for selective permeabilization of the outer membrane. PEF is a process which is able to generate pores within cell membranes, so-called electroporation. It can be readily applied to the culture broth in continuous mode, no additional chemicals are needed, heat generation is relatively low and it is already implemented at industrial scale in the food sector. Yet, studies about PEF assisted extraction of recombinant protein from bacteria are scarce. In the present study, continuous electroporation was employed to selectively extract recombinant Protein A from the periplasm of E. coli. For this purpose, a specifically designed flow-through PEF treatment chamber was deployed, operated at 1.5 kg/h, using rectangular pulses of 3 µs at specific energy input levels between 10.3-241.9 kJ/kg. Energy input was controlled by variation of the electric field strength (28.4-44.8 kV/cm) and pulse repetition frequency (50-1000 Hz). The effect of the process parameters on cell viability, product release and host cell protein (HCP), DNA, as well endotoxin (ET) load were investigated. It was found that a maximum product release of 89% was achieved with increasing energy input levels. Cell death also gradually increased, with a maximum inactivation of -0.9 log10 at 241.9 kJ/kg. The conditions resulting in high release efficiencies while keeping contaminants low were electric field strengths ≤30 kV/cm, and frequencies ≥825 Hz. In comparison to high-pressure homogenization, PEF treatment resulted in 40% less HCP load, 96% less DNA load and 43% less ET load. Therefore, PEF treatment can be an efficient alternative to the cell disintegration processes commonly used in downstream processing.